Konsep Pendidikan Islam Anak Usia Dini Perspektif Syaikh Mustofa Al-Adawi - Anggun Amalia Husna (Bildung: Jurnal Ilmu Pendidikan, 2025)
Education is one of the factors influencing the progress of a nation and state. It plays a role and responsibility in developing the potential of faith, worship, and morals, thus producing superior individuals capable of competing globally. Therefore, the provision of education through families, educational institutions, and the community is a focus of attention, and must collaborate continuously to produce students with noble character. Regarding when a child's education begins, Islam also teaches that education begins while the fetus is still in the womb. Prenatal education is the education provided by the mother to the unborn child while still in the womb. Essentially, the people who provide education during this period are the parents. Nur Islam explained that with the rapid development of technology, more and more people are constantly creating and implementing new discoveries, which keeps humanity abreast of these developments. They have conducted research for years on the benefits and importance of postnatal education. The most important aspect of education today is the development of brain intelligence and language. This age group covers the ages of 0 to 3 years.